2019
DOI: 10.1155/2019/5487293
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural Determinants of the Utilization of Maternal Health Care Services in the Tallensi District in the Upper East Region of Ghana

Abstract: Introduction. The quality maternal health care that women receive during pregnancy and delivery is important for the health of both the mother and the baby. However, most pregnant women do not receive the minimum number of antenatal care (ANC) services (at least 4 times during pregnancy) as recommended by the WHO. This article sought to identify the types of maternal health care services (MHCS) received by women during pregnancy and delivery and after childbirth and women’s reasons for use and nonuse of MHCS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 12 publications
(10 reference statements)
3
46
2
Order By: Relevance
“…We identified that limited decision-making capacity of women, fear of blood transfusion and fear of death at higher level health facilities interfere with the referral. Similar reports have been noted by studies in SSA where men, in-laws and elder decide whether a women should travel [83][84][85]. In rural Uganda, Kyomuhendo [86] noted that women who could endure obstetric pain were considered brave since pregnancy was perceived as a test of endurance.…”
Section: Such Activities Can Focus On Specific Indicators Such As Trisupporting
confidence: 64%
“…We identified that limited decision-making capacity of women, fear of blood transfusion and fear of death at higher level health facilities interfere with the referral. Similar reports have been noted by studies in SSA where men, in-laws and elder decide whether a women should travel [83][84][85]. In rural Uganda, Kyomuhendo [86] noted that women who could endure obstetric pain were considered brave since pregnancy was perceived as a test of endurance.…”
Section: Such Activities Can Focus On Specific Indicators Such As Trisupporting
confidence: 64%
“…Limited decision-making capacity of women, fear of blood transfusion and fear to die in higher level facilities have been noted by similar studies in sSA where men, in-laws and elders decide whether women are allowed to travel [78][79][80]. In rural Uganda, women enduring maternity pain were considered brave since pregnancy was perceived as a test of endurance [81].…”
Section: Discussionmentioning
confidence: 92%
“…Limited decision-making capacity of women, fear of blood transfusion and fear of death at higher level health facilities have been noted by similar studies in SSA where men, in-laws and elder decide whether a women is allowed to travel [80][81][82]. In rural Uganda, women who could endure obstetric pain were considered brave since pregnancy was perceived as a test of endurance [83].…”
Section: Discussionmentioning
confidence: 95%